2018
DOI: 10.1016/j.bone.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Gsα in osteocytes leads to osteopenia due to sclerostin induced suppression of osteoblast activity

Abstract: The stimulatory subunit of G-protein, Gsα, acts as a secondary messenger of G-protein coupled receptors (GPCRs) that primarily activates cAMP-induced signaling. GPCRs, such as the parathyroid receptor (PTHR), are critical regulators of bone formation as shown by number of genetic manipulation studies targeting early osteoblast lineage cells. In this study, we have examined the role of Gsa in osteocytes, the terminally differentiated and most abundant cells of the osteoblast lineage. Mice lacking the stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…These observations in Gnas E1+/-p mice directly correlate with the previous findings in the literature suggesting that impaired Gsα signaling leads to an osteopenic bone phenotype. (36)(37)(38)(39)(40)(41) These findings could have potential implications for patients with PPHP and have yet to be correlated.…”
Section: Discussionmentioning
confidence: 99%
“…These observations in Gnas E1+/-p mice directly correlate with the previous findings in the literature suggesting that impaired Gsα signaling leads to an osteopenic bone phenotype. (36)(37)(38)(39)(40)(41) These findings could have potential implications for patients with PPHP and have yet to be correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Fulzele et al recently reported that deleting Gsα expression utilizing the same Dmp1-Cre used in the present study led to osteopenia due to sclerostin-induced suppression of osteoblast activity. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The osteopenia is associated with increased Sost/ sclerostin expression; treatment with anti-sclerostin antibodies partially rescued the skeletal phenotype, but not the myelopoiesis, thereby suggesting that additional mechanisms control the proliferation of myeloid cells. 11,12 Due to the complexity of the physiological settings and the difficulty of studying osteocytes in vivo, we used in vitro (Ocy454 osteocytic cells) and ex vivo (OEBEs) models 13 to investigate, at the molecular level, the mechanisms by which osteocytes control myelopoiesis. Here we report that osteocytes in vitro and ex vivo secrete Gsα-dependent and independent factors which support myeloid cell proliferation and osteoclast differentiation and function.…”
Section: Discussionmentioning
confidence: 99%